Genetically Targeted Binary Labeling of Retinal Neurons - Zhu, Yongling (Society for Neuroscience, 2014)
A major stumbling block to understanding neural circuits is the extreme anatomical and functional diversity of interneurons. Subsets of interneurons can be targeted for manipulation using Cre mouse lines, but Cre expression is rarely confined to a single interneuron type. It is essential to have a strategy that further restricts labeling in Cre driver lines. We now describe an approach that combines Cre driver mice, recombinant adeno-associated virus, and rabies virus to produce sparse but binary labeling of select interneurons—frequently only a single cell in a large region. We used this approach to characterize the retinal amacrine and ganglion cell types in five GABAergic Cre mouse (Mus musculus) lines, and identified two new amacrine cell types: an asymmetric medium-field type and a wide-field type. We also labeled several wide-field amacrine cell types that have been previously identified based on morphology but whose connectivity and function had not been systematically studied due to lack of genetic markers. All Cre-expressing amacrine cells labeled with an antibody to GABA. Cre-expressing RGCs lacked GABA labeling and included classically defined as well as recently identified types. In addition to the retina, our technique leads to sparse labeling of neurons in the cortex, lateral geniculate nucleus, and superior colliculus, and can be used to express optogenetic tools such as channelrhodopsin and protein sensors such as GCaMP. The Cre drivers identified in this study provide genetic access to otherwise hard to access cell types for systematic analysis including anatomical characterization, physiological recording, optogenetic and/or chemical manipulation, and circuit mapping.